2003
DOI: 10.1073/pnas.0233287100
|View full text |Cite
|
Sign up to set email alerts
|

Routes to S -nitroso-hemoglobin formation with heme redox and preferential reactivity in the β subunits

Abstract: Previous studies of the interactions of NO with human hemoglobin have implied the predominance of reaction channels that alternatively eliminate NO by converting it to nitrate, or tightly complex it on the ␣ subunit ferrous hemes. Both channels could effectively quench NO bioactivity. More recent work has raised the idea that NO groups can efficiently transfer from the hemes to cysteine thiols within the ␤ subunit (cys␤-93) to form bioactive nitrosothiols. The regulation of NO function, through its chemical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
209
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(218 citation statements)
references
References 50 publications
8
209
0
1
Order By: Relevance
“…In one of these proposed mechanisms, MetHb is a reactive intermediate in the production of S-nitrosylated Hb (SNO-Hb); a form of Hb that may subsequently release NO in hypoxic vascular beds. 16,17 Experimental data in support of another proposed mechanism suggest that the stable NO metabolite nitrite (NO 2 -) may provide a physiological source of bioactive NO by deoxygenated hemoglobin (deoxyHb), which can act as a nitrite reductase under allosteric and pH control via the following reaction: Nitrite [NO 2 -] ? deoxyHb ?…”
Section: Résumémentioning
confidence: 99%
“…In one of these proposed mechanisms, MetHb is a reactive intermediate in the production of S-nitrosylated Hb (SNO-Hb); a form of Hb that may subsequently release NO in hypoxic vascular beds. 16,17 Experimental data in support of another proposed mechanism suggest that the stable NO metabolite nitrite (NO 2 -) may provide a physiological source of bioactive NO by deoxygenated hemoglobin (deoxyHb), which can act as a nitrite reductase under allosteric and pH control via the following reaction: Nitrite [NO 2 -] ? deoxyHb ?…”
Section: Résumémentioning
confidence: 99%
“…These results call into question mechanisms, which require increased O 2 affinity as a consequence of HbNO formation. Other investigators have determined that limited exposure of deoxy Hb to NO leads to nitrosylation of β-subunit hemes and subsequent oxygenation leads to the formation of SNO-Hb [12]. Formation of SNO-Hb primarily occurs when NO binds to the β93 Cys residues [13][14][15] and the S-nitroso form of hemoglobin has been observed to exhibit increased O 2 affinity [16].…”
Section: Introductionmentioning
confidence: 99%
“…NO bound as a ferrous nitrosyl adduct [Fe(II)NO] does not exert direct vasodilatory activity (9)(10)(11)(12), because ligand off rates are slow and any NO liberated is rapidly trapped by the surrounding hemes, which are present at relatively high concentrations (excess heme over NO: Ϸ10,000:1) (12). However, work from our laboratories has elucidated conditions under which ␤-chain heme Fe(II)NO complexes can be oxidatively converted to an S-nitrosothiol (Cys␤SNO), which maintains NO bioactivity (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Recent work by us (16) and others (21)(22)(23) has shown that oxidized hemes [Fe(III)], particularly ␤-chain hemes, are competent for this redox activity. Thus, ␤Fe(III)NO meets both the oxidative and structural requirements for SNO-Hb production (7,16,23). In related studies, Pezacki et al (18,24) reported that ␤Fe(III)NO accumulates during deoxygenation of SNO-Hb.…”
mentioning
confidence: 99%
See 1 more Smart Citation